Breathing for 2. Issue 3 (September 2021) - Rudder, M.; Russo, M.; Ventetuolo, C.E.
Abstract : ( N Engl J Med . 2021;384:61–68) This feature contained details about 1 patient's case, with a clinician's commentary interspersed throughout. The case was that of a 29-year-old woman at 26 weeks gestation with undifferentiated connective tissue disease, presenting with cough, and shortness of breath.